2016
DOI: 10.1213/ane.0000000000001505
|View full text |Cite|
|
Sign up to set email alerts
|

The Amount of Fluid Given During Surgery That Leaks Into the Interstitium Correlates With Infused Fluid Volume and Varies Widely Between Patients

Abstract: We found that the increase in intravascular fluid volume caused by intravenous fluid administration was not correlated strongly with the volume of infused fluid. Instead, the amount of fluid leakage into the interstitial space depended on the infused fluid volume. This clinical result supports the revised Starling law, which suggests that intravascular fluid may often leak into the interstitium. More work is needed to better understand the factors governing leakage of infused fluid into the interstitial space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…From the effect size point of view, it is clear that EO has the strongest effect on financial performance and non-financial performance. Therefore, according to Schober et al (2018) or Nishimura et al (2016) or Mukaka (2012), values in the range of 0.00–0.10 are negligible correlation, 0.10–0.39 value is weak and 0.40–0.69 value is a moderate correlation, while 0.70–0.89 value shows a strong relation. Hence, following Schober et al (2018) findings, our constructs have a moderate correlational effect.…”
Section: Resultsmentioning
confidence: 97%
“…From the effect size point of view, it is clear that EO has the strongest effect on financial performance and non-financial performance. Therefore, according to Schober et al (2018) or Nishimura et al (2016) or Mukaka (2012), values in the range of 0.00–0.10 are negligible correlation, 0.10–0.39 value is weak and 0.40–0.69 value is a moderate correlation, while 0.70–0.89 value shows a strong relation. Hence, following Schober et al (2018) findings, our constructs have a moderate correlational effect.…”
Section: Resultsmentioning
confidence: 97%
“…The use of an improper correlation can result in a variety of patterns that produce conflicting results regarding gene expression [ 30 ]. Nishimura et al assessed whether the volume of infused crystalloid fluid is correlated to the amount of interstitial fluid leakage during surgery [ 32 ], and Kim et al studied whether opioid growth factor receptor expression is correlated with cell proliferation in cancer cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that fluid absorption, expressed as the retained fraction of the infused volume, does not depend on the infused fluid volume. In contrast, the filtrated volume, expressed as the excreted fraction of the infused volume, closely correlated with the infused volume [21]. Thus, fluid retention is probably affected mainly by hormonal control, rather than the infused volume.…”
Section: Discussionmentioning
confidence: 82%